Essays on Conrad - Watt, Ian, 1917-1999 (Cambridge University Press, 2000)
Watt's work, Conrad in the Nineteenth Century, was to have been followed by a volume addressing Conrad's later work, but the material for this second volume remained in essay form. It is these essays which form the nucleus of Essays on Conrad.